Salmonella Typhi Bacteria Sensitivity Test To Green Grape (Vitis Vinifera L) Leaf Extract - Eka Nurdianty Anwar; Nita Anggreani (ANJANI Journal (Medical Science & Healthcare Studies), 2021)
Salmonella typhi bacterial infection that causes typhoid fever is one of the highest cases for health, especially in Indonesia. It is necessary to find an alternative treatment using natural ingredients that contain antibacterial to overcome this. The flavonoid content in Green Grape leaves functions as an antibacterial. This study aims to determine the sensitivity of Salmonella typhi bacteria to leaf extract of Green Grape (Vitis vinifera L). The sampling technique was purposive sampling, and the research method was experimental. The concentration of green grape leaf extract made varied from 20%, 40%, 60%, 80% and 100%. The results showed that the inhibition zones formed according to the green grape leaf extract variation were 0 mm, respectively; 2.3mm; 7.5mm; 8mm; and 8.6 mm. The inhibition zone produced by the positive control (+) Ciprofloxacin was 27 mm, while the negative control (-) distilled water produced an inhibition zone of 0 mm. Conclusion : These results concluded that the bacteria Salmonella typhi was resistant to green grape leaf extract.